Therapy hormone PMSG (Oodev) through feed on the reproductive performance of Bileh fish (Rasbora maninjau Lumbantobing, 2014) - Zulfadhli Zulfadhli; Fazril Saputra; Yushinta Fujaya (Depik, 2024)
Efforts to cultivate bileh fish (Rasbora maninjau) experience obstacles in providing seeds due to controlled reproduction in aquaculture containers is still difficult to do. This is due to the slow maturation of fish gonads, which takes a long time. Internal factors, including the hormonal system, influence the reproductive cycle and maturation of fish gonads. This study aims to determine the effect of PMSG (Oodev) hormone administration through feed on the reproductive performance of bileh fish. Experimental research method with CRD experimental design (completely randomized design). The experiment consisted of 4 treatments (P) with three replications. The treatments were PMSG hormone (Oodev) with different doses, namely 0 (P1), 0.5 (P2), 1 (P3), and 2 ml/kg feed (P4). The research phase included the preparation of containers and fish, preparing hormones and feed, rearing, and data collection. Parameters taken and evaluated include gonadosomatic index (GSI), hepatosomatic index (HSI), estradiol concentration, fecundity, and egg diameter. Data were processed and analyzed using statistics (Anova). The results showed that the administration of PMSG hormone (Oodev) through feed had a significant effect on GSI, HSI, estradiol concentration, fecundity, and egg diameter (P0.05). The best treatment was P3 (1 ml/kg) with a GSI value of 8.25%, HSI of 0.41%, estradiol level of 22.46pg/mL, fecundity of 3207 eggs, and egg diameter of 0.85mm.Keywords:PMSGOodevPerformanceReproductionBileh fish